Institutional Resource Management and Parental Satisfaction in Early Childhood Education: Perspectives from Millennial and Gen Z Parents in Indonesia - Upik Elok Endang Rasmani; Siti Wahyuningsih; Bambang Winarji; Jumiatmoko Jumiatmoko; Novita Eka Nurjanah; Nurul Shofiatin Zuhro; Anjar Fitrianingtyas (STAI Hubbulwathan Duri, 2026)
The demographic shift toward Millennial and Generation Z parents has reshaped expectations for early childhood education (ECE), particularly regarding institutional resource management and service quality. This study examines the relationship between institutional resource management and parental satisfaction in ECE settings.A quantitative correlational design was employed with 150 parents in Surakarta, Indonesia, selected through purposive sampling. Data were collected using two Likert-scale instruments measuring institutional resource management (16 items) and parental satisfaction (12 items). Instrument validity was established through expert judgment, and reliability testing using Cronbach’s alpha indicated satisfactory internal consistency. Data were analyzed using Pearson’s correlation coefficient and coefficient of determination.The findings revealed a moderate, statistically significant positive relationship between institutional resource management and parental satisfaction (r = 0.56, p 0.01). The coefficient of determination (R² = 0.31) indicates that 31% of the variance in parental satisfaction is explained by institutional resource management. No significant differences were found between Millennial and Generation Z parents, suggesting convergent expectations regarding transparency, digital documentation, and administrative efficiency.The results highlight the importance of systematic and technology-supported resource management in enhancing parental satisfaction across generational groups. ECE institutions should prioritize managerial transparency, digital service optimization, and responsive administration to align with contemporary parental expectations. Future research should explore additional factors influencing satisfaction and extend analysis across broader educational contexts.